2002
DOI: 10.1080/026404102753576071
|View full text |Cite
|
Sign up to set email alerts
|

Sequential muscle activity and its functional role in the upper extremity and trunk during overarm throwing

Abstract: The proximal-to-distal segmental sequence has been identified in many sports activities, including baseball pitching and ball kicking. However, proximal-to-distal sequential muscle activity has not been identified. The aims of this study were to establish whether sequential muscle activity does occur and, if it does, to determine its functional role. We recorded surface electromyograms (EMGs) for 17 muscles from the upper extremity and abdomen during overarm throwing and detected the onset and peak times as in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
130
0
7

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(144 citation statements)
references
References 37 publications
7
130
0
7
Order By: Relevance
“…Additionally, the forearm extension reached a greater peak angular speed than the arm flexion, suggesting some speed transference from the proximal limb to the distal during movement (Van Gheluwe and Hebbelink, 1985;Putnam, 1993;Hirashima et al, 2002). This could result in an increasing of speed and power on the punch execution.…”
Section: Karate Punch Descriptionmentioning
confidence: 99%
“…Additionally, the forearm extension reached a greater peak angular speed than the arm flexion, suggesting some speed transference from the proximal limb to the distal during movement (Van Gheluwe and Hebbelink, 1985;Putnam, 1993;Hirashima et al, 2002). This could result in an increasing of speed and power on the punch execution.…”
Section: Karate Punch Descriptionmentioning
confidence: 99%
“…In the movement of those segments, the speed peak occurs more proximal to the instant of contact with the bag in the ankle, where the highest value of speed was verified, but increased progressively from the hip to the ankle. This suggests the existence of speed transference from the proximal to the distal segment during movement (Hirashima, Kadota, Sakurai, Kudo & Ohtsuki, 2002), and that could result in an increase of speed and power in the maegeri execution. However, the karateka group achieved a maximum speed earlier than the non-karateka group only for the proximal segment, which may be the result of the training followed by the empirical approach.…”
Section: Discussionmentioning
confidence: 99%
“…for EO on the left side, due to the fact that the trunk rotation movement was initiated by the right side. Hirashima et al (2002) analyzed trunk, shoulder and upper limb muscle action for a ball throw. They confirmed that EO contralateral to the arm which performs the throw is activated first, regarding EO ipsilateral.…”
Section: Emg Peak Mechanic Demand and Clubmentioning
confidence: 99%
“…In explosive and precise motor tasks, as throwing, the trunk muscles sequence plays an important role in the organization of the proximo-distal sequence in order to transfer energy (Hirashima et al, 2002). This mechanism leads to an increase of speed in distal segments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation